Reflection on traditional sporting games: the impact of bodily involvement on empathic dimensions - Dugas, Eric; Ben Ali, Boubaker (Frontiers in Psychology, 2023)
The purpose of this study is to investigate bodily engagement and involvement in traditional sporting games (TSG), with a focus on the development of empathy. Despite the fact that current research on empathy has focused on its emotional component, the name "empathy" alludes to a considerably more profound dimension than emotional engagement. It is about the ability to perceive another person's private life through the exchange of contextual factors provided through interactive sports activities. Our study, based on real-world experiences, demonstrates that Traditional Sporting Games, in particular, stimulate, preserve, or reveal empathic capacities in a number of ways. Games can show and sustain the full potential of empathic dispositions if they are present at a young age. Moreover, by examining empathy through the prism of a TSG, we recognize them as a source of relational empathy and feelings developed to various degrees by direct involvement. As a result, we may define empathy as an integrated pedagogy that can be more successfully conducted via the use of TSG, which are multifaceted because of their internal and external logical systems. Basically, the hypotheses discussed in this research allow us to postulate that the physical gaming involvement of players, such as role changes, has an effect on the individual's empathic dimensions. Additionally, the characteristics of traditional sporting game interaction networks may serve as a source of encouragement or inspiration for a wide range of games (theatrical, social, etc.).